Building resilience through financial inclusion: A review of existing evidence and knowledge gaps - Moore, Danielle; Niazi, Zahra; Rouse, Rebecca; Kramer, Berber (Innovations for Poverty Action, 2019)
Low-income households around the world are particularly vulnerable to shocks, but also the least prepared when a shock hits. The effects of climate change, including floods, droughts, and other weather-related disasters, are adding another layer of risk for already vulnerable households. In this context, it is increasingly important that poor households build resilience—that they strengthen their ability to mitigate, cope, and recover from shocks and stresses without compromising their future welfare. Evidence suggests well-designed financial products and services can play a role in increasing low-income families’ resilience by helping them be prepared for risk, reduce risk, increase investment in the face of risk, and respond when a shock occurs. Yet the role that financial products and services can play in increasing resilience, as well as the most effective design and delivery mechanisms toward that end, is not fully understood. This paper reviews the evidence on financial inclusion and resilience to inform policymakers on effective strategies and makes the call for more research on this timely and relevant topic.